From licensure to residency: structural barriers and policy options in Israel’s residency admission process - Ayala Burger; Alexey Belinsky; Joseph Mendlovic; Daniel Minerbi Padon; Michal Laron (Israel Journal of Health Policy Research, 2026)
Abstract Background Israel faces a growing need for medical professionals due to population growth and aging, yet the number of licensed physicians per capita remains below the OECD average. The gap is particularly evident in the number of medical specialists. One factor contributing to this shortage may be the delay between medical licensure and the commencement of residency training. Objective The objective of this study was to assess the extent to which delays in the commencement of residency programs occur, to identify and analyze barriers that delay the start of residency training among newly licensed physicians in Israel, and to explore possible solutions to optimize this process. Methods This mixed-methods study included a quantitative analysis of administrative datasets from the Israeli Ministry of Health ( n = 18,480), and qualitative analysis based on 31 semi-structured interviews conducted with department heads, residents, and residency candidates between January and August 2023. Results Despite a steady increase in the number of licensed physicians, the median time between licensure and the start of residency has remained constant at approximately four months. According to interviewees’ accounts in the study, delays were often associated with inconsistent and opaque admission processes, regional disparities in hospital demand, and mismatched expectations between candidates and departments, and could in part be explained by the absence of a centralized residency allocation system. Factors such as elective choices during internship and geographic location further influenced the timeline. Interviewees did not commonly report postponing residency for personal reasons. Conclusions Delays in residency placement, compounded by inefficient workforce allocation, may reduce the effective capacity of the healthcare system. A more transparent and structured national framework - similar to those in the US, Canada, and Spain - could help streamline the process and reduce inefficiencies. Policy recommendations include improved data transparency, standardization of admission criteria, and better support for hospitals in peripheral regions. Establishing a unified, annual data reporting system on the physician workforce is a necessary prerequisite for any effective reform or national workforce planning.